Expression of Ki-67 in premalignant and malignant lesion of cervix in tertiary care hospital in Uttar Pradesh - Singh, Pratima; Garg, Kanchan; Singh, Ankita; Tripathi, Shambhavi (International Journal of Research in Medical Sciences, 2023)
Background: cancer is fast emerging as one of the most common causes of death related morbidities throughout the world. As far as India is concerned. Ki-67 is an ideal marker to assess the cellular proliferation. The study aimed to evaluate the proliferative activity by using Ki-67 in premalignant and malignant lesion of cervix. To study the various histomorphology features of cervical lesion and grading it into cervical intraepithelial neoplasia and malignant lesion. To access the expression of Ki 67 in different grade of lesions. Methods: The study was carried in 60 cases of cervical biopsy that included 30 cases of CIN 1, CIN2 and 30 cases of CIN 3, SCC. Ki-67 staining was done on all cases which were diagnosed histologically as CIN or cervical carcinoma. The result was categorized in grading 1,2,3. Results: Ki-67 expression was studied in all cases. There was an increase in the intensity of Ki-67 from CIN to carcinoma. The focal positivity in low grade lesion to diffuse positivity in higher grade lesion was seen in our study. Conclusions: In this study, Ki-67 expression was helpful in differentiating dysplastic lesion from carcinoma and helps in confirming the histopathological diagnosis. Therefore Ki-67 marker could be used as biomarker in the evaluation of the proliferative activity and progressive potential of dysplastic and neoplastic changes.